Family school involvement from the perspective of future teachers (Praxis Educativa, 2021)
The research, of a qualitative nature, analyzes the processes of family participation in schools from the perspective of 42 pre service teachers. The data were obtained from document analysis, the "Incomplete Sentences" strategy, and focus groups. The results point to the existence of languishing participation associated with a receptive or decision-making role on secondary school issues. We also found a type of participation that is restricted to issues involving only the children themselves and that moves away from values such as co-responsibility or equity.
Keywords: parent participation; family; teaching practice; student teachers; teacher training.